Analysis Of Digital Economic Transformation In Improving The Economy Of Home Industries In Kota Pari Village - Wahyu Indah Sari; Annisa Sanny; Ely Delvi Yanti (Proceeding of The International Conference on Economics and Business, 2023)
The purpose of this study was to analyze digital economic transformation towards increasing the income of household entrepreneurs (Case Study: Kota Pari Village, Pantai Cermin District). The specific target in this research is to analyze digital economic transformation towards increasing the income of household business actors in Kota Pari Village, Pantai Cermin District). The hypothesis in this study isE-commerce, E-Money, E-Wallet (Electronic Wallet) simultaneously and partially affect the income of household business actors in Kota Pari Village, Pantai Cermin District. Methodwhich will be used in this study are: Quantitative, where the Quantitative Method in this study relates to data that describes digital economic estimates for increasing the income of home industry entrepreneurs in Kota Pari Village, Pantai Cermin District). The data analysis used is: Quantitative Analysis consisting of Multiple Linear Regression. The results of the study stated that E-commerce significantly affected income, while e-money and e-wallet did not significantly affect the income of business people in Kota Pari Village.